Development of Low Fat Goshtaba with Sodium Alginate - Jalal, Heena; Hussain, Syed Arshad; Bhat, M. Mansoor; Salahuddin, Mir; H, Asif (Journal of Meat Science, 2014)
A study was conducted with an objective to evaluate the effect of sodium alginate @ 0.1% (on weight basis) of batter on the quality of low fat Goshtaba. The raw emulsion was evaluated for physico-chemical parameters (pH, emulsion stability, proximate composition) while cooked product was evaluated for both physico-chemical and sensory parameters. All the physico-chemical parameters of raw emulsion except pH, protein and ash content showed significant (P
Keywords: Fat replacers; Low fat Goshtaba; Meat product; Sodium alginate